FEATURES OF THE PROFESSIONAL PROFILE CONSTRUCTION OF THE MODERN RESEARCHER OF SCIENTIFIC DIVISIONS OF HIGHER MILITARY EDUCATIONAL INSTITUTIONS, MILITARY EDUCATIONAL SUBDIVISIONS OF HIGHER EDUCATION INSTITUTIONS AND SCIENTIFIC INSTITUTIONS IN THE SYSTEM OF - Ryzhykov, V.; Horiacheva, K.; Buryi, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
This scientific article reveals the basic theories of development of a professiographic profile and specifies laws, content, methods, tools, conditions for the development of modern scientific personnel of scientific departments of higher educational institutions in the system of the Ministry of Defense of Ukraine. The professiogram in the case of our scientific search is the basis for creating a portrait of a scientific worker in the system of military science. The principles of creating a portrait of a scientific worker of the university research divisions in the system of the Ministry of Defense of Ukraine must be used both in the process of professional selection of future scientists and in the service characteristic of the scientific worker himself. Unlike the usual formal production characteristics, the professionally substantiated characteristic – the professor's profile in the system of military science – could be a reliable basis for an adequate assessment of the scientist's personality and prediction of his professional efficiency and possible predictable career growth. Professorial structure of the scientific worker of the scientific departments of the higher educational institution in the system of the Ministry of Defense of Ukraine defines the purpose and tasks of the theoretical, practical, self-sufficient, indirect preparedness. The list of requirements of the profession to the psychology of the person and the necessary abilities forms the psychogram of the scientific worker's profession in the system of the Ministry of Education and Science. The professional abilities are understood as sufficiently stable characteristics of the person that change in the process of activity, ensuring its success and improvement. The professional profile of the research worker of the research divisions of the Air Defense Forces, Air Defense Forces, and National Security Forces in the system of the Ministry of Defense of Ukraine contains the following information: general information about the profession and its dynamics; production characteristic of the profession; sanitary and hygienic working conditions with the accentuation of occupational hazards; the list of totality of knowledge and skills required for successful professional activity; characteristics of types and duration of vocational training, the possibility of upgrading the qualification; psychographics. The professiogram allows the effective fulfillment of professional requirements, creating conditions for the development of the personality of a scientific worker and obtaining the product necessary for the society, Determine the most possible ways of acquiring psychological qualities, professional training and retraining, advanced training and requalification, as well as reorientation, if necessary for a particular professor in the system of the Ukrainian Ministry of Defense.
Keywords: professional profile of a research worker; system of scientific work in the Ministry of Defense; theoretical foundations of the development of professiogram; researcher of the military higher education institution